2012
DOI: 10.1007/s12265-012-9414-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Cardiac Allograft Vasculopathy

Abstract: Cardiac allograft vasculopathy remains a major challenge to long-term survival after heart transplantation. Endothelial injury and dysfunction, as a result of multifactorial immunologic and nonimmunologic insults in the donor and the recipient, are prevalent early after transplant and may be precursors to overt cardiac allograft vasculopathy. Current strategies for managing cardiac allograft vasculopathy, however, rely on the identification and treatment of established disease. Improved understanding of mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 155 publications
1
38
0
Order By: Relevance
“…Endothelial injury and dysfunction leads to imbalance between endothelial derived relaxing factors (EDRFs) and endothelium-derived constricting factors (EDCFs). EDCFs promote inflammation and contribute to the development of atherosclerosis by attenuating the action of EDRFs [2,8,27,29,[45][46][47][48][49][50][51][52][53].…”
Section: Immunobiology and Pathogenesis Of Coronary Allograft Vasculomentioning
confidence: 99%
See 3 more Smart Citations
“…Endothelial injury and dysfunction leads to imbalance between endothelial derived relaxing factors (EDRFs) and endothelium-derived constricting factors (EDCFs). EDCFs promote inflammation and contribute to the development of atherosclerosis by attenuating the action of EDRFs [2,8,27,29,[45][46][47][48][49][50][51][52][53].…”
Section: Immunobiology and Pathogenesis Of Coronary Allograft Vasculomentioning
confidence: 99%
“…CAV is multifactorial in origin and is considered to be a form of chronic rejection previously due to the crucial role played by various alloimmune and autoimmune mechanisms in the pathogenesis of CAV [6][7][8]. Although immune mediated factors play a major role, several studies have demonstrated the role of traditional risk factors of coronary artery disease (CAD) in the progression of CAV [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] It is suggested that CAV development begins as a "response to injury," initial endothelial dysfunction followed by intimal hyperplasia as a result of vascular remodeling in response to initial reperfusion injury and repetitive immunological transplant-related endothelial injury. 2) These vascular remodeling and smooth muscle cell (SMC) proliferation are potentiated by inflammatory cytokines, growth factors, and chemotactic factors produced by activated endothelial cells and migrating cells, resulting in the activation of SMC and their migration from the media to the intima. 7) Activated SMC further proliferate and secrete cytokines, which potentiate proliferation and subsequent matrix deposition and luminal narrowing.…”
mentioning
confidence: 99%